Analisa Prestasi Pompa Hidram Dengan Variasi Katub Beban Dan Kondisi Inlet - Santoso, Sigit; Sudia, Budiman; Barata, La Ode Ahmad (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Water transfer in inland areas is still done manually, so we need a water pump with efficiency, technology, economy without the use of electricity and fuel, namely a hydram pump. A hydram pump is a water pump that relies on the momentum of water to raise water. The purpose of this study was to determine the effect of inlet pipe size on pump efficiency, outlet pipe flow rate and the effect of pipe joints on major and minor losses. This research was made with a water source height of 1 m, varying inlet pipes measuring ¾ inch, 1 inch, and 1,5 inch with a length of 5 m, a hydram pump body with a diameter of 1 inch, an air tube with a diameter of 3 inch with a length of 40 cm and an outlet pipe measuring ½ inch. The largest hydram pump efficiency is found in the ¾ inch inlet pipe with 1.94% with an outlet pipe flow rate of 1.79 l/min and the lowest efficiency is in a 1 inch inlet pipe with 1.49% with an outlet pipe flow rate is 1.55 l/min while the major value and the biggest loss value are in the ¾ inch inlet pipe with values of 0.00754 m and 0.678 m and the lowest values are in the 1.5 inch inlet pipe with values of 0.000410 m and 0.019 m so that it can be concluded that the cross-sectional area and the number of connections in the hydram pump installation are very influential on the value of major and minor losses.Keywords: Diameter, Waste Valve, Pipe, Pump